Fabrication and Characterization of Jute Fiber Reinforced Low Density Polyethylene Based Composites: Effects of Chemical Treatment - Miah, M. J.; Khan, M. A.; Khan, R. A. (Journal of Scientific Research, 2011)
Jute fiber reinforced low density polyethylene (LDPE) composites (10-30% fiber, by weight) are prepared by compression molding. Tensile strength (TS), bending strength (BS) and bending elongation (BE) of the composites are increased over LDPE. Jute fiber is treated with monomer (2-hydroxyethyl methacrylate, HEMA) along with two different initiators in methanol solvent. Jute fibers are soaked with 10% HEMA+2% Irgacure-184 (F1-Formulation) and 3% HEMA+2% benzol peroxide (F2-Formulation) and dried at 80ºC for 2 hours then composites are fabricated by compression molding. It is found that due to chemical treatment of the jute fibers, a significant improvement of the mechanical properties of the composites are happened (56% TS, 30% BS and 35% BE) compared to the LDPE. 3%HEMA+2% benzol peroxide treated jute composites found better mechanical properties compared to 10%HEMA+2% Irgacure-184 treated jute composites. Dielectric constant and loss tangent of the composites are increased with increasing temperature up to a transition temperature and then decreased, finally reached to plateau. Scanning Electron Microscopic (SEM) analysis of the fracture side of the composites are carried out and supported better fiber-matrix adhesion due to the chemical treatment. Keywords: Jute fiber; Polyethylene; Composite; Tensile strength; Bending strength; Dielectric constant; Loss tangent. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.6763 J. Sci. Res. 3 (2), 249-259 (2011)